Dynamics of Roads: The Role of Traffic in the Number of Accidents with Fauna - Ribeiro, Tatiana Rolim Soares; Laranja, Ruth Elias de Paula; Barbieri, Camila Barreiros (Sociedade & Natureza, 2022)
The present study sought to acknowledge the effects of velocity and vehicle traffic on animal roadkills on roads nearby Protected Areas (PA) in the Distrito Federal - Brazil. Data on roadkill events for three road segments were superimposed on information on traffic volume, records of speeding infractions, and installation of vertical signs (VSs). The results showed a weak positive correlation between roadkill events and the annual traffic volume (ρ = 0.470; p 0.3) or 500 m (V = 437.5; p> 0.5) of the VSs. The data analysis showed a possible correlation between the fauna that had become accustomed to the road environment that were in collisions between animals and vehicles (AVCs) and the consequent intensification of the edge effect, fragmentation, and isolation of these species in adjacent PAs. It is proposed that new studies evaluate the installation of structures capable of reconnecting the affected areas, the continuity of monitoring projects, and the provision of improved access to data on traffic violations.